Evaluating the Implications of Lineaments on Petroleum Fields: South Sumatra, Indonesia - Tapiwa Frank Kwachara Ngoroyemoto (Geological Engineering Department Universitas Gadjah Mada, 2021)
Declining oil prices has led to a reduction of petroleum exploration as oil production as no longer a lucrative area of investment as in the previous years. Current exploration activities are supported by field work which are intensive considering the resources required. There is need to develop low cost methods to delineate areas of potential hydrocarbon resources. This research uses Land Satellite (Landsat) 8 Operational Land Imager (OLI) for alteration extraction, Shutter Radar Topography Mission (SRTM) for lineament extraction, Geological maps to develop a low cost method of petroleum exploration. The results indicate high OH bearing alterations on the Gumai and Kasai formation, a seal rock. Extensional tectonics is responsible for the migration of petroleum from the subsurface. It is suggested that future exploration be concentrated on the Gumai and Kasai formation based on evidence of micro seepage.